Magnetic Fe3O4 Nanoparticle Biochar Derived from Pomelo Peel for Reactive Red 21 Adsorption from Aqueous Solution - Van Hao Nguyen; Huu Tap Van; Van Quang Nguyen; Xuan Van Dam; L. P. Hoang; L. T. Ha (Journal of Chemistry)
In this study, Fe3O4 nanoparticle-loaded biochar derived from the pomelo peel (FO-PPB) was synthesized and applied as an affordable material for the adsorption of Reactive Red 21 (RR21) in an aqueous solution. The characteristics of FO-PPB were evaluated by scanning electron microscopy (SEM), energy dispersive X-ray spectrometry (EDX), X-ray diffraction (XRD), Raman spectra, Fourier transform infrared spectra (FTIR), and Brunauer–Emmett–Teller (BET) surface area. The adsorption process of FO-PPB with RR21 was evaluated through batch experiments to examine various parameters including solution pH, contact time, adsorbent dose, initial RR21 concentration, and solution temperature. Results show that FO-PPB produced by the impregnation ratio between iron (Fe) and pomelo peel biochar (PPB) of 5 : 1 (w/w) had the best adsorption performance. The adsorption capacities of PPB and FO-PPB at optimum experimental conditions (solution pH 3, contact time of 60 min, solution temperature of 40°C, initial RR21 concentration of 300 mg/L, and adsorbent dose of 2 g/L) were 18.59 and 26.25 mg/g, respectively. The adsorption isotherms of RR21 on PPB and FO5-PPB were described well by Langmuir and Sips models with high R2 values of 0.9826 and 0.9854 for FO5-PPB and 0.9701 and 0.9903 for PPB, respectively. The obtained data also well matched the pseudo-first-order and pseudo-second-order models with R2 values ≥ 0.96. Chemisorption through sharing or electronic exchange was determined as the main adsorption mechanism.